Juridical Review of Standard Clauses in Car Rental Agreements Based on Good Faith Principles - Shavananda Shalsabilzahra H; Herwastoeti; Dwi Ratna Indri Hapsari (Universitas Muhammadiyah Malang, 2023)
Rental agreements are usually made in writing in a standardized form, namely the content, form and closing have been standardized unilaterally by the business actor. This agreement is coercive and causes losses for the lessee and even an imbalance in the position between consumers and producers. This study aims to: (1) determine the contents of the standard clauses in the car rental agreement at Komando Rent a Car whether or not they are in accordance with the principle of good faith (2) to determine the legal consequences of including the standard clause in the car rental agreement at Komando Rent a car. The type of research used in this study is empirical juridical by using data collection techniques through interviews and literature studies. The results of the study show that: (1) the car rental agreement at Komando Rent a Car is not in accordance with the principle of good faith because there is a standard clause in the form of delegation of responsibility for business actors to the detriment of one of the parties, does not reflect a sense of justice and violates the law (2 ) the legal consequence of the inclusion of a standard clause which contains the transfer of responsibility for this business actor is that the agreement is null and void and can be subject to imprisonment and fines. Abstrak Perjanjian sewa biasanya dilakukan secara tertulis yang sudah dalam bentuk baku yaitu isi, bentuk serta penutupannya telah dibakukan secara sepihak oleh pelaku usaha. Perjanjian ini bersifat memaksa dan menimbulkan kerugian bagi pihak penyewa bahkan terdapat ketidakseimbangan posisi antara konsumen dan produsen. Penelitian ini bertujuan untuk: (1) mengetahui isi klausula baku pada perjanjian sewa menyewa mobil di Komando Rent a Car telah sesuai atau tidak dengan asas itikad baik (2) untuk mengetahui akibat hukum dari pencantuman klausula baku pada perjanjian sewa menyewa mobil di Komando Rent a Car. Jenis penelitian yang digunakan dalam penelitian ini adalah yuridis empiris dengan menggunakan teknik pengumpulan data melalui wawancara dan studi kepustakaan. Hasil penelitian menunjukkan bahwa: (1) perjanjian sewa menyewa mobil di Komando Rent a Car tidak sesuai dengan asas itikad baik karena terdapat klausula baku berupa pelimpahan tanggung jawab pelaku usaha sehingga merugikan salah satu pihaknya, tidak mencerminkan rasa keadilan dan melanggar Undang-Undang (2) akibat hukum dari pencantuman klausula baku yang memuat pengalihan tanggung jawab pelaku usaha ini adalah perjanjian tersebut batal demi hukum dan dapat dikenai sanksi penjara dan denda.